Food Technology forecasting: A based bibliometric update in functional chocolates - Balcázar-Zumaeta, C.R.; Castro-Alayo, E.M.; Muñóz-Astecker, L.D.; Cayo-Colca, I.S.; Velayarce-Vallejos, F. (Elsevier, 2023)
Technology forecasting (TF) based on bibliometric tools allows knowing the technological trends of developed topics based on experience and current knowledge, thus anticipating future changes. To reduce hunger and improve nutrition, the food-based topic is of central concern, especially functional food. Among these, various studies on chocolates have been performed. On a global scale, these products are at the level of patents, with China leading it, vastly outperforming the cocoa-producing countries. Though no known functional chocolates are sold under that specific name, chocolates on the market serve as "carriers" of bioactive compounds. Unfortunately, they cannot be attributed to health properties since these properties have to be evaluated with in vitro, in vivo, and clinical studies. Launching functional chocolate on the market is possible; however, it would be a long-term process involving previous stages such as studying its ingredients' bioactive properties, laboratory-level product development, functional properties, and quality and acceptance parameters. For research purposes, it is possible to speak of functional chocolates, potentially functional chocolates, or chocolates enriched with bioactive compounds since the development of research does not necessarily involve launching the product on the market.
Keywords: Bibliometric; Bioactive; Cocoa; Patents; Health; Food; Market; https://purl.org/pe-repo/ocde/ford#4.03.03